Technology Acceptance Model To Analyze Satisfaction And Loyalty Of Users Of Satuguru Blockchain-Based Online Media Platform - Widyanto, Widyanto; Ariyani, Nafiah (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
To find out user responses to the Satuguru Platform. One method that can facilitate this need is to use the methodTechnology Acceptance Model (TAM). The phenomenon that occurs with the loyalty of Satuguru users is quite a lot of usersmove to another platform.. In this research, Technology Acceptance Model (TAM) will be used to understand how users accept and adopt new technologies, especially in terms of security and content with Blockchain. This study aims to determine and analyze the effect of perceived usefulness and perceived ease of use on loyalty mediated by user satisfaction on the Satuguru Blockchain-based online media platform. The method used in this research is quantitative with a descriptive approach. The sample of this research is 140 rRespondents selected by customers who are users of the Satuguru Blockchainbased Online media platform.The data collection method uses a questionnaire that has been tested for validity and reliability. This study uses the SmartPLS 3 software method. The results of the study show that there is a direct or indirect influence on perceived usefulness and perceived ease of use on loyalty mediated by user satisfaction on the Satuguru Blockchain-based Online media platform.